Emergence and Scale-up of Frugal Innovations: The Relevance of University-Industry Interaction - Darío Reyes Reina (Universidad Alberto Hurtado, 2021)
This article analyses the emergence and scale-up of frugal innovations supported by university-industry interactions in the Colombian context. We conducted semi-structured interviews with eight researchers from the National University of Colombia, who participated in activities to transfer technology to society through frugal innovations. Results highlight the social role of the Colombian university and the motivations of the participating researchers to develop frugal innovations. Three benefits of the university-industry interaction to develop and upscale frugal innovations were identified and described: a) the exchange of specialised knowledge that helps to do incremental improvements on frugal innovations; b) the strengthening of distribution and marketing strategies of innovation, supporting its implementation in different contexts; and c) advantages in scaling up production. The relevance of these findings to understand frugal innovation processes and their implications for designing support services by university technology transfer offices are discussed.